2016
DOI: 10.1021/acsami.6b06565
|View full text |Cite
|
Sign up to set email alerts
|

SnS2- Compared to SnO2-Stabilized S/C Composites toward High-Performance Lithium Sulfur Batteries

Abstract: The common sulfur/carbon (S/C) composite cathodes in lithium sulfur batteries suffer gradual capacity fading over long-term cycling incurred by the poor physical confinement of sulfur in a nonpolar carbon host. In this work, these issues are significantly relieved by introducing polar SnO2 or SnS2 species into the S/C composite. SnO2- or SnS2-stabilized sulfur in porous carbon composites (SnO2/S/C and SnS2/S/C) have been obtained through a baked-in-salt or sealed-in-vessel approach at 245 °C, starting from met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…This means that both MoS 2 /S and MCNT/MoS 2 /S electrode have good reversibility. The position of the peak is consistent with that recorded in the previous literature [45][46][47]. In CV curves of MCNT/S and MCNT/MoS 2 /S, the cathodic and anodic peaks position are almost the same.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This means that both MoS 2 /S and MCNT/MoS 2 /S electrode have good reversibility. The position of the peak is consistent with that recorded in the previous literature [45][46][47]. In CV curves of MCNT/S and MCNT/MoS 2 /S, the cathodic and anodic peaks position are almost the same.…”
Section: Resultssupporting
confidence: 90%
“…Nevertheless, the cathodic and anodic peak value of MCNT/MoS 2 /S (peaks I: 1.7 mA; peak III: 3.6 mA) are higher than MCNT/S (peaks I:1.4 mA; peak III:1.9 mA) in figure 4(d). It suggested that the electrochemically active of MCNT/MoS 2 is higher than MCNT [45]. The CV curves of MoS 2 /S cathode and MCNT/MoS 2 /S cathode are almost identical for the first three cycles respectively, exhibiting relatively good capacity retention.…”
Section: Resultsmentioning
confidence: 95%
“…The spectroscopic studies and first‐principles calculations consistently demonstrate the coupled chemical interaction of Co 9 S 8 with Li 2 S n that relies on S n 2− –Co δ + and Li + –S δ − (of Co 9 S 8 ) binding. Here, the as‐synthesized Co 9 S 8 exhibits far superior LiPS's adsorbent ability than the most popular carbon materials, enabling LSB cathodes to have stable cycling performance …”
Section: Strategiesmentioning
confidence: 99%
“…The design of multi-architectural and multi-functional cathode materials has the potential to overcome these challenges and has been one of the most researched strategies in recent years. Currently, physical routes including capillary force absorption [14,[51][52][53][54][55][56][57], shell coating [58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75], and chemical routes containing heteroatom-doped carbons [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90] and metal-based additives [91][92][93][94][95][96][97][98][99]…”
Section: Fundamental Studies and Materials Selectionmentioning
confidence: 99%